Case Report: Epi-endocardial bridges in refractory cavotricuspid isthmus-dependent atrial flutter: technical analysis of epi-endocardial breakthrough - Matteucci, Andrea; Pandozi, Claudio; Russo, Maurizio; Galeazzi, Marco; Lombardi, Enrico; Mariani, Marco Valerio; Lavalle, Carlo; Colivicchi, Furio (Frontiers in Cardiovascular Medicine, 2024)
Background: Typical isthmus-dependent atrial flutter (AFL) is traditionally treated through radiofrequency (RF) ablation to create a bidirectional conduction block across the cavo-tricuspid isthmus (CTI) in the right atrium. While this approach is successful in many cases, certain anatomical variations can present challenges, making CTI ablation difficult.Methods: We enrolled four patients with typical counter-clockwise AFL who displayed an epicardial bridge at the CTI. Patients underwent high-resolution mapping of the right atrium and CTI ablation.Results: Post-mapping identified areas of early focal activation outside the lesion line which suggested the presence of an epi-endocardial bridge with an endocardial breakthrough, confirmed by recording a unipolar rS pattern on electrograms at that site. A stable CTI block was achieved in all patients only after ablation at the site of the epi-endocardial breakthrough.Conclusions: The presence of an epicardial bridge at the CTI, allowing conduction to persist despite endocardial ablation, should be considered in challenging cases of CTI-dependent AFL. Understanding this phenomenon and utilizing appropriate mapping and ablation techniques are essential for achieving successful and lasting CTI block.